Relasi Islam dan Negara: Wacana Keislaman dan Keindonesiaan - Cecep Supriadi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
Islam is not only religion but also a political and legal ideology that has been realized in a world of power and widespread in many countries to this day. Islam showed the whole culture that includes religion and state which is based on the concept of the state and the pure Islamic teachings. The relationship between Islam and the State in the context of Indonesian-ness has always been an interesting thing to be discussed. Mutual attraction between the Nationalists Islam and the Secular Nationalists still continues to this day. Religious life in Indonesia is unique. In the constitution that was approved since the inception of this state, is still being debated in the realm of application. The application of moral values perfectly into the goal for the state and statehood. On the other hand, the life of the compound causing some groups want to live in a liberal and secular. System based on their assumption, making Indonesia as a secular state can accommodate minorities. That will create an ideal state of life. However, the Indonesian constitution that exists today asserted that Indonesia is not a secular state.